Theoretical model for management of nursing research groups - Greici Capellari Fabrizzio; Alacoque Lorenzini Erdmann; José Luís Guedes dos Santos (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To develop a theoretical model for management of research groups in nursing graduate programs. Method: This is a Grounded Theory developed in a stricto sensu nursing graduate program of a public university. Data collection was conducted from April to October 2018 and the theoretical sample consisted of 21 participants arranged in three sample groups. Results: Research activities are linked to research groups, which require human, material and financial resources to develop their studies. These conditions call for management strategies and national and international interactions that result in theoretical, scientific and technological development of the profession. Final considerations: The theoretical model for management of research groups can serve as a guide for graduate programs in nursing and health for planning the work process and so that they can contribute with research of great impact for society.